A Synchronization Control System for Converters Based on FPGA - LI Miao; QIU Yuefeng; ZHANG Shaoyun (Kongzhi Yu Xinxi Jishu)
To avoid problems of PWM edge jitter and sampling offset in the asynchronous control system of converters, this paper proposed a design scheme for synchronous control system of converters based on FPGA. The proposed scheme, which uses FPGA as the core of synchronous beat control of a converter system, can realize the synchronization of sampling control, algorithm calculation and SVPWM output of the converter system. Experimental results show that the proposed scheme can not only effectively solve the excessive requirement of data bandwidth and the existence of PWM edge jitter of converter asynchronous control system, but also can improve the sampling performance of the converter asynchronous system. As so, the control accuracy of the converter can be greatly improved.